Großflächige Tracerversuche zum Einfluss von Sohlbaggerungen auf Entwicklung des Grundwassereintrags - Matthias Munz; Daniel Strasser; Hermann-Josef Lensing; Sascha E. Oswald (Grundwasser, 2025)
Zusammenfassung Die an der Schleuse Brandenburg vorherrschenden Potenzialunterschiede führen zu einer permanenten Infiltration von Oberflächenwasser aus dem oberen Vorhafen des Bauwerks in den oberflächennahen Grundwasserleiter, vergleichbar mit den Verhältnissen bei einer Uferfiltration. Durch die geringen Fließgeschwindigkeiten im Oberwasser kommt es zu Ablagerungen von Feinsedimenten, die lokal zu Kolmationshorizonten führen können. Mittels kontinuierlicher Wasserstands- und Temperaturmessungen sowie wiederholten, großflächigen Tracerversuchen wurde untersucht, inwieweit die Störung der potenziellen Kolmationsschicht das Infiltrationsmuster von Oberflächenwasser in den Grundwasserleiter, die Grundwasserstände sowie das Strömungsfeld beeinflusst. Die Entfernung von mehreren Dezimetern schwach toniger, schluffiger Sande durch Sohlbaggerung führte zu keiner relevanten Gesamtänderung des Grundwasserspiegels oder der Grundwassertemperatur. Die detaillierte Auswertung der beiden Tracerversuche vor und nach der Sohlbaggerung zeigt jedoch, dass lokal relevante Veränderungen des Grundwasserströmungsfeldes aufgetreten sind. Durch die eingriffsbedingte Veränderung der dominanten Infiltrationszonen im Oberwasser des Bauwerks wurden die Grundwasserfließwege verkürzt und dadurch Verweilzeiten im Aquifer hin zu Grundwassermessstellen um den Faktor 2,5 reduziert.

Clonal genomic population structure of Beauveria brongniartii and Beauveria pseudobassiana : Pathogens of the common European cockchafer ( Melolontha melolontha L.) - Chiara Pedrazzini; Stephen A. Rehner; Hermann Strasser; Niklaus Zemp; Rolf Holderegger; Franco Widmer; Jürg Enkerli (Environmental Microbiology, 2024)
Beauveria brongniartii is a fungal pathogen that infects the beetle Melolontha melolontha , a significant agricultural pest in Europe. While research has primarily focused on the use of B. brongniartii for controlling M. melolontha , the genomic structure of the B. brongniartii population remains unknown. This includes whether its structure is influenced by its interaction with M. melolontha , the timing of beetle‐swarming flights, geographical factors, or reproductive mode. To address this, we analysed genome‐wide SNPs to infer the population genomics of Beauveria spp., which were isolated from infected M. melolontha adults in an Alpine region. Surprisingly, only one‐third of the isolates were identified as B. brongniartii , while two‐thirds were distributed among cryptic taxa within B. pseudobassiana , a fungal species not previously recognized as a pathogen of M. melolontha . Given the prevalence of B. pseudobassiana , we conducted analyses on both species. We found no spatial or temporal genomic patterns within either species and no correlation with the population structure of M. melolontha , suggesting that the dispersal of the fungi is independent of the beetle. Both species exhibited clonal population structures, with B. brongniartii fixed for one mating type and B. pseudobassiana displaying both mating types. This implies that factors other than mating compatibility limit sexual reproduction. We conclude that the population genomic structure of Beauveria spp. is primarily influenced by predominant asexual reproduction and dispersal.

Behavioral response of three subterranean pests (Agriotes lineatus, Diabrotica virgifera virgifera, Phyllopertha horticola) to the fungal volatile organic compounds 1-octen-3-ol and 3-octanone - Pierre-Antoine Bourdon; Maria Zottele; Zeeshan Zafar; Ian Baxter; Audun Midthassel; Arben Myrta; Katharina F. Wechselberger; Hermann Strasser; Tariq M. Butt (Arthropod-Plant Interactions, 2023)
The volatile organic compounds (VOCs) 1-octen-3-ol and 3-octanone produced by the entomopathogenic fungus Metarhizium brunneum are known to have pesticidal properties at high doses against a range of invertebrate pests. Very little is known about their behavior-modifying (semiochemical) properties. This study focused on investigating the behavioral responses of three subterranean crop pests, wireworm ( Agriotes lineatus ) , western corn rootworm ( Diabrotica virgifera virgifera ), and garden chafer ( Phyllopertha horticola ), to relatively low doses of 1-octen-3-ol and 3-octanone. The behavior of wireworms and corn rootworms were slightly influenced by the VOCs, yet not significantly. Western corn rootworms appeared to be slightly attracted by 100 µl and 200 µl 1-octen-3-ol and 100 µl dose of 3-octanone, respectively but slightly repelled by the higher dose of 3-octanone. Wireworms appeared to be slightly repelled by 1-octen-3-ol and high dose 3-octanone, but slightly attracted by the 100 µl dose of 3-octanone. The VOCs had no significant impact on garden chafer. In silico studies showed that corn rootworm odorant binding proteins (OBPs) had a strong binding affinity of 1-octen-3-ol and high dose 3-octanone, indicating that these VOCs can be detected and recognized by corn rootworm. OBPs are well conserved between species; thus, wireworm and garden chafer OBPs should also be able to bind with the VOCs. Further trials will be done to confirm that VOCs could be used as semiochemicals. Appropriate formulation of the VOCs should increase their efficacy and prevent rapid dissipation of the VOCs.

Correction: Impact of river reconstruction on groundwater flow during bank filtration assessed by transient three-dimensional modelling of flow and heat transport - Wei-shi Wang; Sascha E. Oswald; Thomas Gräff; Hermann-Josef Lensing; Tie Liu; Daniel Strasser; Matthias Munz (Hydrogeology Journal, 2020)

Correction: Impact of river reconstruction on groundwater flow during bank filtration assessed by transient three-dimensional modelling of flow and heat transport - Wei-shi Wang; Sascha E. Oswald; Thomas Gräff; Hermann-Josef Lensing; Tie Liu; Daniel Strasser; Matthias Munz (Hydrogeology Journal, 2020)

Impact of river reconstruction on groundwater flow during bank filtration assessed by transient three-dimensional modelling of flow and heat transport - Wei-shi Wang; Sascha E. Oswald; Thomas Gräff; Hermann-Josef Lensing; Tie Liu; Daniel Strasser; Matthias Munz (Hydrogeology Journal, 2020)
Bank filtration (BF) is an established indirect water-treatment technology. The quality of water gained via BF depends on the subsurface capture zone, the mixing ratio (river water versus ambient groundwater), spatial and temporal distribution of subsurface travel times, and subsurface temperature patterns. Surface-water infiltration into the adjacent aquifer is determined by the local hydraulic gradient and riverbed permeability, which could be altered by natural clogging, scouring and artificial decolmation processes. The seasonal behaviour of a BF system in Germany, and its development during and about 6 months after decolmation (canal reconstruction), was observed with a long-term monitoring programme. To quantify the spatial and temporal variation in the BF system, a transient flow and heat transport model was implemented and two model scenarios, ‘with’ and ‘without’ canal reconstruction, were generated. Overall, the simulated water heads and temperatures matched those observed. Increased hydraulic connection between the canal and aquifer caused by the canal reconstruction led to an increase of ~23% in the already high share of BF water abstracted by the nearby waterworks. Subsurface travel-time distribution substantially shifted towards shorter travel times. Flow paths with travel times <200 days increased by ~10% and those with <300 days by 15%. Generally, the periodic temperature signal, and the summer and winter temperature extrema, increased and penetrated deeper into the aquifer. The joint hydrological and thermal effects caused by the canal reconstruction might increase the potential of biodegradable compounds to further penetrate into the aquifer, also by potentially affecting the redox zonation in the aquifer.

The socioeconomic benefits of biological control of western corn rootworm Diabrotica virgifera virgifera and wireworms Agriotes spp. in maize and potatoes for selected European countries - Emmanuel O. Benjamin; Giselher Grabenweger; Hermann Strasser; Justus Wesseler (Journal of Plant Diseases and Protection, 2018)

Biological control of the European cockchafer: persistence of Beauveria brongniartii after long-term applications in the Euroregion Tyrol - Johanna Mayerhofer; Jürg Enkerli; Roland Zelger; Hermann Strasser (BioControl, 2015)